The Urgency to Renew Bankruptcy Law Requirements and Summary Proof in Indonesia - Tan, David; Sudirman, Lu; Fiorentine, Jasisca (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The provisions pertaining to bankruptcy and summary proof in Law Number 37 of 2004 present various drawbacks in their application, particularly impacting debtors. Debtors can be declared bankrupt with relative ease, and the requirement for declaring bankruptcy does not directly indicate the debtor’s insolvency. This can present difficulties for other creditors, as the leniency in bankruptcy requirements for debtors is viewed as means to accelerate debt resolution, even though not all face the same circumstances. This research will focus on the issues regarding the urgency of revising Law Number 37 of 2004, specifically with regard to the conditions for bankruptcy and summary proof. The method used in this research is the doctrinal legal research method, which entails scrutinizing literary sources, legal theories or principles, research journals, and legislative regulations to analyze the subject of the research. Furthermore, a comparative approach is adopted to evaluate the development of Indonesian law by examining the bankruptcy legal frameworks in France and the Netherlands. The study concludes that the pressing need for amendments to the conditions for bankruptcy and summary proof in Law Number 37 of 2004 necessitates a responsive legal system. This can be achieved through a comprehensive review of problematic regulations. Therefore, the incorporation of additional measures, such as an insolvency test and a proactive approach by judges, establishes a regulatory mechanism that can be viewed as a responsive outcome in the future.